Insights from a codesigned dynamic modelling study of child and adolescent obesity in Australia - Alison Hayes; Rebecca Wyse; Anna Lene Seidler; Kylie E Hunter; Rebecca K Golley; Louise A Baur; Anthony D Okely; Kenny Lawson; Jo-An Occhipinti; Louise Freebairn; Simon Keith Chiu; Joseph Carrello; et al. (BMJ Public Health)
Introduction Child and adolescent obesity is associated with a range of immediate health issues and influences obesity in adulthood. The complex nature of health determinants that contribute to obesity makes it challenging to deliver effective public health interventions. This research presents insights from a system dynamics model of childhood and adolescent obesity aimed at supporting evidence-based decision-making.Methods A system dynamics model was developed using the best available evidence and data, with input from research and industry experts to map the hypothetical causal structure of the factors contributing to childhood and adolescent obesity in Australia. The model was calibrated to fit the historical prevalence of obesity (R2=0.97, mean squared error (MSE)=4.94E-04). Intervention-based scenarios were simulated to examine how changes in environmental factors and health-related behaviours may affect the prevalence of obesity. The potential economic benefits of the scenarios were estimated from changes in population healthcare spending and quality of life compared with base model projections.Results A series of interventions were explored in the model, including changes in early childhood behaviours, changes to diet and physical activity in childcare and school settings, financial support for organised sports and sugar-sweetened beverage taxation. The most promising individually implemented intervention scenario for reducing the prevalence of childhood and adolescent obesity was a sugar-sweetened beverage tax (0.57 percentage points and 0.61 percentage points, respectively) and government funding of organised sports (0.42 percentage points and 0.63 percentage points, respectively). When all interventions were implemented in combination, childhood obesity was reduced by 1.43 percentage points and 1.81 percentage points in adolescents.Conclusions The findings highlight the challenges faced by policy-makers and public health practitioners working to reduce childhood and adolescent obesity. Insights from the model emphasise the value of public health programmes over the life course. Implementing initiatives with broad reach that support healthy choices may reduce obesity, resulting in a healthier Australian population.